Echocardiographic Criteria to Differentiate Constrictive Pericarditis From Restrictive Cardiomyopathy: A Meta-analysis - Carlos Diaz-Arocutipa, MD; María Chumbiauca, MS; Hector M. Medina, MD, MPH; Adrian V. Hernandez, MD, PhD; Lourdes Vicent, MD (CJC Open, 2023)
Background: To assess the diagnostic accuracy of the Mayo Clinic echocardiographic criteria for differentiating between constrictive pericarditis and restrictive cardiomyopathy. Methods: We searched electronic databases for the date range from their inception to July 1, 2022. The index tests were the Mayo Clinic echocardiographic criteria. We performed a bivariate random-effects model to estimate the pooled sensitivity and specificity, each with 95% confidence interval (CI). The area under the curve of the summary receiver operator characteristic curves, with 95% CI, was also calculated. Results: We included 17 case-control studies involving 889 patients. The pooled sensitivity and specificity (95% CI), respectively, were as follows: ventricular septal shift, 82% (60%-94%) and 78% (65%-87%); respiratory variation in mitral inflow ≥ 14.6%, 71% (51%-85%) and 82% (66%-91%); septal eʹ velocity ≥ 8 cm/s, 83% (80%-87%) and 90% (83%-95%); septal eʹ velocity/lateral eʹ velocity ≥ 0.88, 74% (64%-82%) and 81% (70%-88%); and hepatic vein ratio in expiration ≥ 0.79, 73% (65%-81%) and 71% (19%-96%). The area under the curve of the summary receiver operator characteristic curves varied from 0.75 to 0.85, with overlapping CIs across index tests. Conclusions: Our meta-analysis suggests that all echocardiographic parameters from the Mayo Clinic criteria have good diagnostic accuracy for differentiating between constrictive pericarditis and restrictive cardiomyopathy. Résumé: Contexte: Évaluation de l’exactitude diagnostique des critères échocardiographiques de la clinique Mayo visant à faire la distinction entre une péricardite constrictive et une cardiomyopathie restrictive. Méthodologie: Nous avons effectué une recherche dans des bases de données électroniques pour la période s’étendant de leur date de création au 1er juillet 2022. Les tests de concordance portaient sur les critères échocardiographiques de la clinique Mayo. Nous avons réalisé un modèle à effets aléatoires et à deux variables afin d’estimer la sensibilité et la spécificité en fonction des données regroupées, chacune avec un intervalle de confiance (IC) à 95 %. L’aire sous la courbe des courbes caractéristiques sommaires de la performance du test, avec un IC à 95 %, a également été calculée. Résultats: Nous avons inclus 17 études cas-témoins comptant 889 patients. Selon les données groupées, la sensibilité et la spécificité (IC à 95 %), respectivement, étaient les suivantes : déplacement du septum interventriculaire, 82 % (60 à 94 %) et 78 % (65 à 87 %); variation respiratoire lors du remplissage mitral ≥ 14,6 %, 71 % (51 à 85 %) et 82 % (66 à 91 %); vitesse eʹ mesurée en septal ≥ 8 cm/s, 83 % (80 à 87 %) et 90 % (83 à 95 %); rapport vitesse eʹ mesurée en septal/vitesse eʹ mesurée en latéral ≥ 0,88, 74 % (64 à 82 %) et 81 % (70 à 88 %); et rapport veineux hépatique lors de l’expiration ≥ 0,79, 73 % (65 à 81 %) et 71 % (19 à 96 %). L’aire sous la courbe des courbes caractéristiques sommaires de la performance du test variait de 0,75 à 0,85, avec des IC se chevauchant dans les tests de concordance. Conclusions: Notre méta-analyse laisse entendre que tous les paramètres échocardiographiques de la clinique Mayo ont une bonne exactitude diagnostique pour faire la distinction entre la péricardite constrictive et la cardiomyopathie restrictive.